Revisiting international administrative law as a legal discipline - Handrlica, Jakub (Array, 2019)
The term “international administrative law” is understood in two separate ways. On one hand, the authors (diritto internazionale amministrativo) used this term regarding the administrative competencies of various international administrative unions, as provided by applicable international conventions. On the other hand, other authors (e.g. Karl Neumeyer, Paul Négulescu, Giuseppe Biscottini) used the term to exclusively refer to the norms of national law (diritto amministrativo internazionale, droit administratif international, internationales Verwaltungsrecht), which address certain foreign elements. This article follows the second understanding of the term “international administrative law.” For a long time, these norms had been quite rare in administrative law and, consequently, the legal scholarship did not pay much attention to the discipline of international administrative law. However, most recently, the sources of EU law increasingly require reflection of certain foreign elements in the norms of administrative law. In this respect, this article argues that international administrative law represents a legal discipline that is fully capable of addressing those problems arising by the application of these norms in administrative law.